Social media marketing : strategies in utilizing consumer-generated content - Moriuchi, Emi (Business Expert Press, 2019)
The author explains why it is even more important today that brands need consumer voices to advocate their brands. In this lively and practical book, she uses theories to explain consumers psychology and offers practical examples of which social media platforms are conducive to CGC and why. In addition, she explains how consumers use CGC in different countries, the importance of influencer marketing, and ultimately teaches the strategy of using CGC effectively.- Resumé vydavatel
Keywords: internetový marketing; internetová reklama; sociální média; Internet marketing; Internet advertising; social media; elektronické knihy; monografie; electronic books; monographs